THE APPLICATION OF FINITE ELEMENT METHOD FOR MHD VISCOUS FLOW OVER A POROUS STRETCHING SHEET - Mahmood, R.; Sajid, M. (The Nucleus, 2020)
This work is concerned with the magnetohydrodynamic (MHD) viscous flow due to a porous stretching sheet. The similarity solution of the problem is obtained using finite element method. The physical quantities of interest like the fluid velocity and skin friction coefficient is obtained and discussed under the influence of suction parameter and Hartman number. It is evident from the results that MHD can be used to control the boundary layer thickness.